Apolipoprotein E4 reduces evoked hippocampal acetylcholine release in adult mice - Dolejší, Eva; Liraz, Ori; Rudajev, Vladimír; Zimčík, Pavel; Doležal, Vladimír; Michaelson, Daniel M (Journal of neurochemistry, 2016)
Apolipoprotein E4 (apoE4) is the most prevalent genetic risk factor for Alzheimer's disease. We utilized apoE4-targeted replacement mice (approved by the Tel Aviv University Animal Care Committee) to investigate whether cholinergic dysfunction, which increases during aging and is a hallmark of Alzheimer's disease, is accentuated by apoE4. This revealed that levels of the pre-synaptic cholinergic marker, vesicular acetylcholine transporter in the hippocampus and the corresponding electrically evoked release of acetylcholine, are similar in 4-month-old apoE4 and apolipoprotein E3 (apoE3) mice. Both parameters decrease with age. This decrease is, however, significantly more pronounced in the apoE4 mice. The levels of cholinacetyltransferase (ChAT), acetylcholinesterase (AChE), and butyrylcholinesterase (BuChE) were similar in the hippocampus of young apoE4 and apoE3 mice and decreased during aging. For ChAT, this decrease was similar in the apoE4 and apoE3 mice, whereas it was more pronounced in the apoE4 mice, regarding their corresponding AChE and BuChE levels. The level of muscarinic receptors was higher in the apoE4 than in the apoE3 mice at 4 months and increased to similar levels with age. However, the relative representation of the M1 receptor subtype decreased during aging in apoE4 mice. These results demonstrate impairment of the evoked release of acetylcholine in hippocampus by apoE4 in 12-month-old mice but not in 4-month-old mice. The levels of ChAT and the extent of the M2 receptor-mediated autoregulation of ACh release were similar in the adult mice, suggesting that the apoE4-related inhibition of hippocampal ACh release in these mice is not driven by these parameters. Evoked ACh release from hippocampal and cortical slices is similar in 4-month-old apoE4 and apoE3 mice but is specifically and significantly reduced in hippocampus, but not cortex, of 12-month-old apoE4 mice. This effect is accompanied by decreased VAChT levels. These findings show that the hipocampal cholinergic nerve terminals are specifically affected by apoE4 and that this effect is age dependent.
Keywords: Age Factors; myši; Mice, Inbred C57BL; Alzheimer's disease (AD); guanosin 5'-O-(3-thiotrifosfát); mužské pohlaví; tritium; vezikulární transportní proteiny acetylcholinu; Acetylcholine; apolipoprotein E4; cholin-O-acetyltransferasa; Apolipoprotein E3; Male; Mice, Transgenic; Tritium; Apolipoprotein E4; Receptors, Muscarinic; apolipoprotein E3; acetylcholine release; N-methylskopolamin; Guanosine 5'-O-(3-Thiotriphosphate); receptory muskarinové; hipokampus; myši inbrední C57BL; N-Methylscopolamine; myši transgenní; Animals; hippocampus; Mice; zvířata; apolipoprotein E4 (apoE4); acetylcholin; Vesicular Acetylcholine Transport Proteins; Hippocampus; Choline O-Acetyltransferase; věkové faktory